2001
DOI: 10.1289/ehp.01109173
|View full text |Cite
|
Sign up to set email alerts
|

Associations of blood levels of PCB, HCHS, and HCB with numbers of lymphocyte subpopulations, in vitro lymphocyte response, plasma cytokine levels, and immunoglobulin autoantibodies.

Abstract: Pentachlorophenol (PCP), hexachlorocyclohexane-[alpha], -beta, and -[gamma] (HCH-[alpha], -beta, and -[gamma]), polychlorinated biphenyls (PCBs), and hexachlorobenzene (HCB) are widely distributed industrial chemicals. They are suspected to induce immunologic impairments in exposed individuals. We examined dose-response relationships of blood levels of these chemicals with cellular (numbers of lymphocyte subpopulations, in vitro lymphocyte response) or humoral (plasma cytokine levels, immunoglobulin autoantibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…The allergic Th2 phenotype is characterized by secretion of cytokines that promote immunoglobulin E (IgE) production resulting in allergies. This suggestion is in agreement with findings of Daniel and co-workers, who reported an association between DDE and interleukin-4, a Th2 cytokine [39]. In addition, our interpretation that DDE may be associated with an allergy-like response is supported by the distribution of aeroallergen-specific IgE results over the four DDE exposure levels.…”
Section: Discussionsupporting
confidence: 93%
“…The allergic Th2 phenotype is characterized by secretion of cytokines that promote immunoglobulin E (IgE) production resulting in allergies. This suggestion is in agreement with findings of Daniel and co-workers, who reported an association between DDE and interleukin-4, a Th2 cytokine [39]. In addition, our interpretation that DDE may be associated with an allergy-like response is supported by the distribution of aeroallergen-specific IgE results over the four DDE exposure levels.…”
Section: Discussionsupporting
confidence: 93%
“…The percentages of monocytes and lymphocytes demonstrated significantly lower levels in the exposure group, and both of them showed negative correlations with PCBs. As previously reported, occupational PCB-exposed individuals with higher levels of persistent chemicals in their blood demonstrated lower levels of T lymphocyte counts (Daniel et al, 2001). Another cross-sectional study also reported that lymphocyte numbers were lower in the highest PCB exposure groups (Serdar et al, 2014).…”
Section: Discussionmentioning
confidence: 55%
“…However, the results have not been consistent. Although some studies have reported positive associations (Daniel et al 2001; Langer et al 2002), other studies failed to do so (Schoenroth et al 2004; Tsuji 2000; Tsuji et al 1999; Yu et al 1998). …”
Section: Discussionmentioning
confidence: 99%